Cervical Cancer Screening and Prevention in Low- and Middle-Income Countries: A Perspective from Bangladesh - Deeba, Iztiba Mallik; Hossain, Mohammad Sorowar (Bangladesh Journal of Microbiology, 2023)
Cervical cancer is a major public health concern for women worldwide, particularly in low- and middle-come countries (LMICs). Despite a large number of women (nearly 58 million) are at risk of this preventable cancer, the issue of cervical cancer has not become a public health priority in Bangladesh. The understanding of the challenges and opportunities in Bangladesh about cervical cancer would provide valuable insights for other LMICs also. In this article, we review the epidemiology, risk factors, awareness and treatment of cervical cancer in the context of Bangladesh. Due to lack of awareness and an organized national screening program, the majority of patients are generally diagnosed at the advantaged stages of disease, in spite of having a big window of screening opportunity at precancer stage. Most LMICs lack resources for developing a parallel health service system dedicated for cancer prevention and management. In this context, we propose some recommendations including a cost-effective screening strategy by capitalizing available resources of COVID-19 diagnostic and GenXpert labs, and an innovative female-centric primary healthcare workers and high school-based approaches for generating awareness on cervical cancer risk factors, screening and vaccination. Our proposed strategy could also be effective for other similar settings in LMICs. Bangladesh J Microbiol, Volume 39, Number 2, December 2022, pp 76-82